Characterization of protective gloves stiffness: Development of a multidirectional deformation test method - Harrabi, Lotfi; Dolez, Patricia I.; Vu-Khanh, Toan; Lara, Jaime; Tremblay, Guy; Nadeau, Sylvie; Larivière, Christian (Safety science, 2008)
A test method was developed to characterize the stiffness of protective gloves as perceived by users by applying multidirectional deformations to the material to simulate the behavior of gloves in use. Twenty eight protective glove models covering a broad range of stiffness were characterized with two mechanical methods: the new multidirectional test and the Kawabata Evaluation System for Fabrics (KESF) based on uniaxial deformations. Some differences were observed between the longitudinal and transversal KESF measurements even for isotropic materials. A psychophysical evaluation test was also carried out by thirty subjects in order to rank the gloves. The correlation between the psychophysical evaluation and the new multidirectional test method was higher ( r = 0.93) than those obtained with the KESF measurements along the longitudinal and transversal directions (respectively r = 0.79 and 0.76). This better performance of the new test method is attributed to the difference in the type of applied deformations: uniaxial for the KESF test vs. multidirectional for the test method developed in this study. Thus, this multidirectional test method, which applies more realistic mechanical deformations, appears as a promising tool for the characterization of protective gloves stiffness as perceived by users.